2004
DOI: 10.1097/01.asn.0000120369.92378.54
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Chimerism Occurs Regularly in Renal Allografts and Is Not Correlated to Outcome

Abstract: Abstract. Recent studies have demonstrated an integration of recipient-derived progenitor cells into solid allografts with differentiation into parenchymal cells. Whether or to what extent this phenomenon influences allograft outcome has still to be elucidated. To detect epithelial chimerism tubular cells were harvested from sequential renal allograft biopsy samples by laser microdissection in 36 patients. Recipient-derived cells were detected by short-tandem repeat-based genotyping. In cases with gender-misma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 33 publications
5
23
2
Order By: Relevance
“…At the time of biopsy, the presence of endothelial chimerism correlates moderately with the presence of tubular atrophy, but the presence of endothelial chimerism has no relation to a vast number of clinical parameters, including graft function and outcome. This is in line with the results from a recent study in epithelial chimerism in tubular epithelial cells of renal transplants [8], because also in this study, chimerism did not correlate with allograft function [8].…”
Section: Discussionsupporting
confidence: 94%
“…At the time of biopsy, the presence of endothelial chimerism correlates moderately with the presence of tubular atrophy, but the presence of endothelial chimerism has no relation to a vast number of clinical parameters, including graft function and outcome. This is in line with the results from a recent study in epithelial chimerism in tubular epithelial cells of renal transplants [8], because also in this study, chimerism did not correlate with allograft function [8].…”
Section: Discussionsupporting
confidence: 94%
“…Using this marker, our group recently reported that TGFβ, presented either in solution or on the surface of T lymphocytes, could induce EMT of cultured human RCEC, and also showed a spatial association between EMT and intratubular T cells in kidney transplant biopsy sections (4). The possibility that EMT plays a major role during the development of chronic renal allograft nephropathy is entirely consistent with studies showing that relatively few recipient‐derived cells re‐populate the parenchyma of damaged human kidneys following transplantation (30).…”
Section: Discussionsupporting
confidence: 77%
“…This phenomenon also indicated that recipient-derived cells might actively participate in the regeneration of injured tubular epithelium after ACR. Recently, Mengel et al reported that epithelial microchimerism by re- cipient-derived cells was not correlated to morphologic or functional outcome in renal allografts (12), which seems conflicting with our present results and also with some other types of organ transplantation (13)(14).…”
Section: Discussioncontrasting
confidence: 75%